(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The essay is a reading of the hagiographic dossier of Saint Miniato of Florence from a diachronic and synchronic perspective at the same time. The analysis reveals two fundamental aspects: i) a stratification of the text that is more articulated than hitherto imagined and, thus, a multi-secular continuity of the cult; ii) the questioning, at the beginning of the 11th century, of the veracity of the news about the location of the martyr’s body on the suburban hill, where it had been believed for centuries that he was buried. The analysis illuminates a more general process, namely the renegotiation of the symbolic heritage constituted by the relics of martyrs at the beginning of the 11th century. Of the ’renegotiation’, the discursive context is reconstructed here, up to the recomposition of the mid-11th century.